Desenvolvimento de catalisadores para aplicação em reações de formação de ligações C-C estereosseletivas - Rocha, Mariane [UNIFESP] (2017)
In this work the immobilization of organocatalysts in ordered mesoporous silicas, type SBA-15, was studied in order to obtain a heterogeneous system and to facilitate the recycling of the organocatalyst and also to improve its catalytic efficiency. In this context, organocatalysts derived from L-proline were synthesized and incorporated into the SBA-15 by adsorption and chemically linked by functionalization with organosilane. The catalytic systems obtained were characterized and used as catalysts in asymmetric aldol reactions, using cyclohexanone and p-nitrobenzaldehyde as reagents. The organocatalysts were also incorporated into SBA-15 by in situ adsorption, with the catalytic reaction reagents themselves. The incorporation of the organocatalytic agents did not cause any structural damage to the SBA-15, maintaining its mesoporous structure. However, there was a reduction of the surface area and pore volume indicating the insertion of organic species in the mesopores of the SBA-15. Since the incorporation was higher when the adsorption method was used, in addition, the in situ process adsorption resulted in a larger amount of material within the mesopores. The results of the catalytic tests showed that the organocatalysts incorporated to SBA-15 by in situ adsorption were more efficient, as they resulted in greater conversion and reactivity selectivity.